2006
DOI: 10.1021/cb600352f
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule Inhibitor for Phosphatase and Tensin Homologue Deleted on Chromosome 10 (PTEN)

Abstract: Phosphatase and tensin homologue deleted on chromosome 10 (PTEN), a phosphoinositide 3-phosphatase, is an important regulator of insulin-dependent signaling. The loss or impairment of PTEN results in an antidiabetic impact, which led to the suggestion that PTEN could be an important target for drugs against type II diabetes. Here we report the design and validation of a small- molecule inhibitor of PTEN. Compared with other cysteine-based phosphatases, PTEN has a much wider active site cleft enabling it to bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 70 publications
6
131
0
Order By: Relevance
“…The IC50s for PTP1B is ~20-fold higher and ~13-fold higher for SopB as compared to PTEN. Taken all this observations together, VO-OHpic seems to be the choice of compounds, if PTEN is to be selectively inhibited, which is in agreement with our earlier investigation [11].…”
Section: Pten Inhibition Assaysupporting
confidence: 91%
See 2 more Smart Citations
“…The IC50s for PTP1B is ~20-fold higher and ~13-fold higher for SopB as compared to PTEN. Taken all this observations together, VO-OHpic seems to be the choice of compounds, if PTEN is to be selectively inhibited, which is in agreement with our earlier investigation [11].…”
Section: Pten Inhibition Assaysupporting
confidence: 91%
“…An activation at a concentration of 50 nM can already be detected which is in good agreement with the known in vitro VO-OHpic potency [11,24], demonstrating the good cell permeability of this inhibitor. The fact that 50 nM of VO-OHpic is sufficient to exert cellular effects also means that the chance of hitting other phosphatases can be reduced to a minimum as the determined IC50s for other Cx5R phosphatases is at least 10-fold higher as shown in table 3.…”
Section: Measuring Pten Inhibition In Cellulosupporting
confidence: 85%
See 1 more Smart Citation
“…HCT116 cells were pre-treated with the PTEN inhibitor SF1670 (2 lM) for 24 h (untreated HCT116 cells served as control); treated cells were subsequently plated under non-adherent conditions with added MET (60 lM), Lun (2 lm), or Gen (2 lM). SF1670 binds to the PTEN active site, resulting in elevated phosphatidylinositol (3,4,5) triphosphate signaling (Rosivatz et al 2006). We found that inhibition of PTEN activity increased colonosphere formation relative to control cells (Fig.…”
Section: Soy Bioactive Components Alter Hct116 Cell Viability Apoptomentioning
confidence: 73%
“…Therefore, enhancing PTEN function by targeting its regulatory machinery can be an effective cancer therapeutic approach. In addition, we suggest that the potential of PTEN targeting in treating other diseases, especially diabetes, should be reconsidered (Kurlawalla-Martinez et al, 2005;Wijesekara et al, 2005;Rosivatz et al, 2006;Sasaoka et al, 2006;Stiles et al, 2006). Previously, the enthusiasm of PTEN inhibition for treating diabetes was dampened because of the undesired tumorigenic effect that might be associated with such treatment.…”
Section: Discussionmentioning
confidence: 98%